2013
DOI: 10.1053/j.gastro.2012.11.022
|View full text |Cite
|
Sign up to set email alerts
|

Weight-Independent Effects of Roux-en-Y Gastric Bypass on Glucose Homeostasis via Melanocortin-4 Receptors in Mice and Humans

Abstract: Background & Aims Roux-en-Y gastric bypass (RYGB) improves glucose homeostasis independently of changes in body weight by unknown mechanisms. Melanocortin-4 receptors (MC4R) have weight-independent effects on glucose homeostasis, via autonomic neurons, and might also contribute to weight loss after RYGB. We investigated whether MC4Rs mediate effects of RYGB, such as its weight-independent effects on glucose homeostasis, in mice and humans. Methods We studied C57BL/6 mice with diet-induced obesity, MC4R-defic… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

9
91
1

Year Published

2014
2014
2020
2020

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 70 publications
(102 citation statements)
references
References 49 publications
9
91
1
Order By: Relevance
“…Interestingly, a study employing intracerebroventricular administration of a specific MC4R antagonist in RYGBP and sham-operated rats demonstrated that while central MC4R blockade led to doubling of food intake and weight regain, the reduction in meal size produced by RYGBP was unaffected (123). Restoration of MC4R in key preganglionic autonomic motor neurons of Mc4r-null mice demonstrated that MC4R expression in these neurons was important for RYGBP-induced reductions in food intake, but the effect was greater for RYGBP effects on energy expenditure (124). While these studies highlight the critical role of the melanocortin pathway in regulation of energy intake, they establish that central melanocortin signaling is not the critical mechanism responsible for the anorectic effects of RYGBP, in particular, the RYGBP-induced reduction in meal size, which is clearly central to the feeding changes observed in humans after RYGBP (41).…”
Section: Role Of the Mc4r Pathwaymentioning
confidence: 99%
“…Interestingly, a study employing intracerebroventricular administration of a specific MC4R antagonist in RYGBP and sham-operated rats demonstrated that while central MC4R blockade led to doubling of food intake and weight regain, the reduction in meal size produced by RYGBP was unaffected (123). Restoration of MC4R in key preganglionic autonomic motor neurons of Mc4r-null mice demonstrated that MC4R expression in these neurons was important for RYGBP-induced reductions in food intake, but the effect was greater for RYGBP effects on energy expenditure (124). While these studies highlight the critical role of the melanocortin pathway in regulation of energy intake, they establish that central melanocortin signaling is not the critical mechanism responsible for the anorectic effects of RYGBP, in particular, the RYGBP-induced reduction in meal size, which is clearly central to the feeding changes observed in humans after RYGBP (41).…”
Section: Role Of the Mc4r Pathwaymentioning
confidence: 99%
“…Most of the recent animal studies and some studies in humans have examined the role of the melanocortin system, which seems to be central to many peripheral and brain-derived stimuli that control eating and body weight (55,92,93,157). In humans, the sufficiency of one functional MC4r gene for effective RYGB outcome was indicated in some studies, including RYGB or VSG-operated humans (157).…”
Section: Cns Eating and Body Weight Controls After Rygbmentioning
confidence: 99%
“…Most of the recent animal studies and some studies in humans have examined the role of the melanocortin system, which seems to be central to many peripheral and brain-derived stimuli that control eating and body weight (55,92,93,157). In humans, the sufficiency of one functional MC4r gene for effective RYGB outcome was indicated in some studies, including RYGB or VSG-operated humans (157). However, the important role of the melanocortin system was supported by findings in humans with a specific variant of the MC4 gene [MC4r(I251L)], which is associated with a better metabolic status; in fact, carriers of this variant had improved surgery outcome (92,157).…”
Section: Cns Eating and Body Weight Controls After Rygbmentioning
confidence: 99%
See 1 more Smart Citation
“…79 However, because all these vagal lesions did not differentiate between afferents and efferents, the conclusions are limited and await more selective vagal manipulations such as targeted genetic deletions in mouse models of RYGB. 37,80 CONCLUSIONS Studies using forced over-or under-feeding paradigms in rodents clearly demonstrate defense of a new body weight set point after RYGB and sleeve gastrectomy, but the underlying mechanisms have not yet been fully revealed. Specifically, it is not clear what signals are generated in the re-arranged gut, how they reach the brain, and where exactly in the brain they act to evade a state of hunger and hypo-metabolism that is typically encountered with dieting-induced weight loss.…”
Section: Role Of Microbiota-host Interactionsmentioning
confidence: 99%